Haplotype analysis of cytochrome oxidase (CO1) gene of aedes albopictus isolated from Tawau, Sabah: an asian perspective / Nor Fadhilah Mohd Adam - Mohd Adam, Nor Fadhilah (2017)
The spread and the rise of Ae. albopictus population from its native range in Southeast Asia was resulting in increasing of dengue outbreak and dengue cases reported in Malaysia. Present vector control programs seems to become ineffective and lose their potential to combat the rapid expansion of Ae. albopictus mosquitoes in all over the nation. Studies on Ae. albopictus population genetic structure and genetic diversity was considered as the best option for better understanding on this mosquito species origin and its evolutions from time to time. Thus, this study was conducted to analyze and identify the genetic diversity among Ae. albopictus isolated from Tawau, Sabah in Malaysia using a mitochondrial DNA (mtDNA) marker, Cytochrome oxidase (CO1) gene. Molecular study started with genomic DNA extraction of three individual adult female Ae. albopictus mosquitoes isolated from Tawau, Sabah and three USM laboratory strains (USM LS) followed by the amplifications of the extracted samples using three different sets of CO1 primer. PCR products were sent for sequencing and the obtained sequenced were subjected to BioEdit software for concatenation process, involving the joining of the three fragments that have been amplified. BLAST analysis revealed high similarities between the samples with the reference sequences obtained from NCBI GenBank database proved the used of Ae. albopictus in this study. Subsequently, the concatenated sequences were aligned using ClustalX2.1 together with another 12 reference sequences from NCBI GenBank representing four Asian countries (China, Taiwan, Japan and Singapore). Haplotype network and haplotype analysis of all the samples was constructed using TCS network via PopART and DNasp software respectively. This study disclosed an interesting finding whereby 18 different haplotypes from the total of 18 samples tested, with haplotype (gene) diversity (Hd value) of 1.000 was detected. In conclusion, the finding in this study revealed the merit of using the concatenated CO1 gene as a genetic marker. A longer fragment of CO1 gene was amplified and sequenced (1420bp), which helped the polymorphisms determination within Tawau samples.